Pengaruh Financial Literacy, Lotus of Control, dan Self Efficacy terhadap Financial Behavior - Rita Atari; Erin Soleha (Universitas Negeri Surabaya, 2023)
Financial Behavior is important for students because it determines their financial condition and achievement of their financial goals, especially in addressing the issue of the 2023 recession, it is necessary to improve financially so that students are able to prepare themselves as well as someone's provision to face this crisis if it does happen. This study aims to show that there is a relationship between self-efficacy, locus of control, and financial literacy on financial behavior. This research used 100 samples obtained from the Pelita Bangsa University student population, management study program class of 2019, with the sample determination method, namely non-probability sampling and a purposive sampling approach. This research is a type of quantitative research in which the data is obtained primarily from questionnaires and secondarily through literature studies. The data analysis technique uses Partial Least Square (PLS) through testing the outer model and inner model coefficients with the help of SmartPLS software. The research findings show that financial literacy, self-efficacy, and locus of control have a significant effect partially or simultaneously on the financial behavior of Pelita Bangsa University students.